A Clinically Relevant Variant of the Human Hydrogen Sulfide-Synthesizing Enzyme Cystathionine β-Synthase: Increased CO Reactivity as a Novel Molecular Mechanism of Pathogenicity?. (22nd March 2017) - Vicente, João B.; Colaço, Henrique G.; Malagrinò, Francesca; Santo, Paulo E.; Gutierres, André; Bandeiras, Tiago M.; Leandro, Paula; Brito, José A.; Giuffrè, Alessandro
Abstract : The human disease classical homocystinuria results from mutations in the gene encoding the pyridoxal 5′-phosphate- (PLP-) dependent cystathionine β -synthase (CBS), a key enzyme in the transsulfuration pathway that controls homocysteine levels, and is a major source of the signaling molecule hydrogen sulfide (H2 S). CBS activity, contributing to cellular redox homeostasis, is positively regulated by S -adenosyl-L -methionine (AdoMet) but fully inhibited upon CO or NO binding to a noncatalytic heme moiety. Despite extensive studies, the molecular basis of several pathogenic CBS mutations is not yet fully understood. Here we found that the ferrous heme of the reportedly mild p.P49L CBS variant has altered spectral properties and markedly increased affinity for CO, making the protein much more prone than wild type (WT) CBS to inactivation at physiological CO levels. The higher CO affinity could result from the slightly higher flexibility in the heme surroundings revealed by solving at 2.80-Å resolution the crystallographic structure of a truncated p.P49L. Additionally, we report that p.P49L displays impaired H2 S-generating activity, fully rescued by PLP supplementation along the purification, despite a minor responsiveness to AdoMet. Altogether, the results highlight how increased propensity to CO inactivation of an otherwise WT-like variant may represent a novel pathogenic mechanism in classical homocystinuria.